Recent Developments and Challenges in COVID-19 Care - M., Veena (Innovational: Journal of Nursing and Healthcare, 2024)
The COVID-19 pandemic, caused by the SARS-CoV-2 virus, has fundamentally transformed global health care, revealing both critical vulnerabilities and significant innovations in patient care. This review delves into the latest advancements in COVID-19 care, with a particular focus on the evolution of therapeutic strategies, the rapid and widespread adoption of telemedicine, and the pressing challenges in addressing mental health during the pandemic. Key developments include significant progress in antiviral and immunomodulatory treatments, which have proven essential in managing severe COVID-19 cases. Concurrently, telemedicine has emerged as a revolutionary tool in health-care delivery, enabling the continuity of care despite widespread disruptions. The pandemic’s profound psychological impact has necessitated the creation of new crisis intervention models, highlighting the importance of adaptable and accessible mental health services. The existing research for this review was conducted using comprehensive searches of databases such as PubMed, Springer, and other reputable sources. This approach ensured that the most current and relevant studies on COVID-19 care, therapeutic advancements, telemedicine, and mental health support were included in the analysis. In conclusion, the ongoing adaptation and application of these innovations will be crucial in determining the resilience and effectiveness of health-care systems in future crises. The lessons learned from the COVID-19 pandemic will continue to inform and shape the evolution of global health-care strategies.